Manajemen Sarana dan Prasarana Pendidikan di Madrasah Diniyah Takmiliyah Awwaliyah Nurul Hidayah Kertawinangun - Sayuti, Muhamad Deden Jalaludin (Journal of Islamic Education Leadership, 2023)
Management of Educational and Infrastructure at Madrasah Diniyah Taklimiyah Awwaliyah Nurul Hidayah Kertawinangun. Management of Facilities and Infrastructure is an instrument in improving the quality of students, as well as what was carried out at the MDTA Nurul Hidayah in Kertawinangun village. This study aims to determine the planning, procurement, supporting, and inhibiting factors for managing facilities and infrastructure at MDTA Nurul Hidayah, Kertawinangun village. The ability to identify a facility and infrastructure management can be seen from the planning, implementation, supporting, and inhibiting factors. This study uses a qualitative approach with an analytical descriptive method. Data collection techniques in this study were done through interviews, observation, and documentation. At the same time, the data analysis is done through data reduction, data display, and conclusion. The results of this study indicate that Planning for the Management of Facilities and Infrastructure for MDTA Nurul Hidayah in Kertawinangun village was carried out involving the MDTA Nurul Hidayah community in Kertawinangun village. The Madrasa implements a process divided into five stages: procurement, inventory, use, maintenance, and disposal. Supporting factors are human resources and committees, while inhibiting factors are limited costs, especially in adding areas and buildings